Aging and Options to Halt Declining Immunity to Virus Infections - Palacios-Pedrero, Miguel Ángel; Osterhaus, Albert D. M. E.; Becker, Tanja; Elbahesh, Husni; Rimmelzwaan, Guus F.; Saletti, Giulietta (Frontiers in Immunology, 2021)
Immunosenescence is a process associated with aging that leads to dysregulation of cells of innate and adaptive immunity, which may become dysfunctional. Consequently, older adults show increased severity of viral and bacterial infections and impaired responses to vaccina-tions. A better understanding of the process of immunosenescence will aid the development of novel strategies to boost the immune system in older adults. In this review, we focus on major alterations of the immune system triggered by aging, and address the effect of chronic viral infections, effectiveness of vaccination of older adults and strategies to improve im-mune function in this vulnerable age group.